2017
DOI: 10.1111/dth.12563
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study to compare efficacy of topical triamcinolone acetonide 0.1% oral paste, oral methotrexate, and a combination of topical triamcinolone acetonide 0.1% and oral methotrexate in moderate to severe oral lichen planus

Abstract: Topical corticosteroids are considered to be the most effective treatment for oral lichen planus (OLP). Methotrexate has been found to be effective in extensive cutaneous lichen planus. The objectives of the study were to evaluate the clinical efficacy and safety of topical triamcinolone 0.1% oral paste, oral methotrexate and a combination of these in symptomatic moderate-to- severe OLP. Forty-five patients were recruited and were allocated to three treatment arms with 15 patients in each treatment arm. They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…Intermittent therapy may be helpful here. In certain situations, the use of topical steroids can be associated with other systemic drugs to speed up the clinical response: accordingly, a prospective observational study has shown the combination of topical triamcinolone acetonide 0.1% in combination with oral methotrexate has better outcomes than the two drugs independently in patients with moderate‐to‐severe oral LP …”
Section: High‐potency Topical Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent therapy may be helpful here. In certain situations, the use of topical steroids can be associated with other systemic drugs to speed up the clinical response: accordingly, a prospective observational study has shown the combination of topical triamcinolone acetonide 0.1% in combination with oral methotrexate has better outcomes than the two drugs independently in patients with moderate‐to‐severe oral LP …”
Section: High‐potency Topical Steroidsmentioning
confidence: 99%
“…Alongside with the use as single therapy, systemic methotrexate may be used in combination with topical steroids and tacrolimus, which resulted in higher efficacy . In case of a combinated therapy, it was suggested that methotrexate can be reduced to 2.5–7.5 mg weekly …”
Section: Methotrexatementioning
confidence: 99%
“…This percentage is relatively lower than our results of 73.3% complete resolution. Another study revealed that combination of low dose methotrexate and triamcinolone is a better treatment modality in Oral lichen planus 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Authors reported partial response or better in 15 (83.3%) patients, with pain reduction assessed by Visual Analogue scale (VAS) score (18). Chauhan et al (19) compared efficacy of triamcinolone acetonide 0.1% oral paste, oral methotrexate, and combination of the 2 in moderate to severe OLP. Fortyfive patients were treated for 16 weeks.…”
Section: Methotrexatementioning
confidence: 99%